Chinese mergers and acquisitions on the European market in the chemical sector - Łopacińska, Karolina (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The article focuses on the case study analysis of selected Chinese companies which concluded agreements such as mergers and acquisitions on the European market in the chemical sector between 2005 and 2015, that is: the agreements between BorsodChem Zrt and Wanhua Industrial Group, as well as between Pirelli and National Chemical Corp. The purpose of the paper is to recognise the premises and results of those investments. Therefore, first specifics of the Chinese chemical sector and the characteristics of the analysed companies have been presented. Then the analysis of the premises, the strategic goals, as well as the course of the agreements and the implications of these forms of integration, in the context of shaping the economic strength, position and direction of strategic growth of companies on the European market have been presented
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 486, s. 24-35
Keywords: mergers; acquisitions; M&A; Chinese companies; chemical sector; fuzje; przejęcia; chińskie przedsiębiorstwa; sektor chemiczny